2021
DOI: 10.3389/fneur.2021.613967
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of MRI Volumetry in Epilepsy Patients With Hippocampal Sclerosis Supported Through a Random Forest Automatic Classification Algorithm

Abstract: Introduction: Several methods offer free volumetry services for MR data that adequately quantify volume differences in the hippocampus and its subregions. These methods are frequently used to assist in clinical diagnosis of suspected hippocampal sclerosis in temporal lobe epilepsy. A strong association between severity of histopathological anomalies and hippocampal volumes was reported using MR volumetry with a higher diagnostic yield than visual examination alone. Interpretation of volumetry results is challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…This is particularly relevant for future studies since as LITT becomes more common, less histopathological samples will be available, and therefore the definition of lesional and non‐lesional MTLe will have to be done exclusively based on MRI. Fortunately, past studies have established that hippocampal volumetry is an excellent predictor of hippocampal sclerosis (Bernasconi, 2006 ; Princich et al, 2021 ), therefore as we recruit more subjects for a larger GluCEST study, group assignments will likely be defined by hippocampal volumetry together with MRI lesional status. Future studies from our group aim at acquiring a larger sample size of MTLe‐L, MTLe‐NL and controls subjects in order to perform a well‐powered study where differences between these groups can be explored in both an ROI and voxel‐wise fashion without the need for asymmetry measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly relevant for future studies since as LITT becomes more common, less histopathological samples will be available, and therefore the definition of lesional and non‐lesional MTLe will have to be done exclusively based on MRI. Fortunately, past studies have established that hippocampal volumetry is an excellent predictor of hippocampal sclerosis (Bernasconi, 2006 ; Princich et al, 2021 ), therefore as we recruit more subjects for a larger GluCEST study, group assignments will likely be defined by hippocampal volumetry together with MRI lesional status. Future studies from our group aim at acquiring a larger sample size of MTLe‐L, MTLe‐NL and controls subjects in order to perform a well‐powered study where differences between these groups can be explored in both an ROI and voxel‐wise fashion without the need for asymmetry measurements.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for future studies since as LITT becomes more common, less histopathological samples will be available, and therefore the definition of lesional and non-lesional MTLe will have to be done exclusively based on MRI. Fortunately, past studies have established that hippocampal volumetry is an excellent predictor of hippocampal sclerosis (Bernasconi, 2006;Princich et al, 2021), therefore as we recruit more subjects for a larger GluCEST study, group assignments will likely be defined by hippocampal volumetry together with MRI lesional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis, it was found that the volume of the hippocampus decreased in the course of TLE. Moreover, hippocampal volumes ipsilateral to the hippocampal sclerosis side were significantly reduced compared with controls and also with the non-lesional side [ 32 ]. Additionally, some patients with left exhibited ipsilateral hippocampal atrophy and segmental volume depletion of the cornu ammonis, dentate gyrus, and stratum radiatum-lacunosum-moleculare.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that few previous studies have addressed HS-related atrophy at the subfield level; moreover, the results have been inconsistent. [24][25][26][27] Two recent studies have reported on the use of automated segmentation. One study reported significant reductions in the volume of the contralateral presubiculum in patients with left MTLE.…”
Section: Volume Of the Whole Hippocampus And Hippocampal Subfieldsmentioning
confidence: 99%